2023
DOI: 10.1177/15269248221145046
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Posttransplant Anemia With Overall Mortality and Cardiovascular Outcomes Among Kidney Transplant Recipients

Abstract: Introduction: Posttransplant anemia is a common finding after kidney transplantation. A previous meta-analysis reported an association between anemia and graft loss. However, data on cardiovascular outcomes have not yet been reported. Objective: We conducted an updated meta-analysis to examine the association between posttransplant anemia and outcomes after transplantation including cardiovascular mortality in adult kidney transplant recipients. Methods: We comprehensively searched the databases of MEDLINE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Following renal transplantation, in addition to common metabolic and infectious complications, patients also encounter haematological abnormalities. 18 In our study population, the most prevalent blood-related complication was PTA. Renal transplant patients experience anemia at various periods after transplantation, and the cause of anemia differs with time.…”
Section: Discussionmentioning
confidence: 82%
“…Following renal transplantation, in addition to common metabolic and infectious complications, patients also encounter haematological abnormalities. 18 In our study population, the most prevalent blood-related complication was PTA. Renal transplant patients experience anemia at various periods after transplantation, and the cause of anemia differs with time.…”
Section: Discussionmentioning
confidence: 82%
“…A meta-analysis addressing the effect of anemia on graft survival including 11 observational studies and 11,632 KTRs reported a consistent association between anemia and poor graft outcome, 32 as confirmed by several subsequent studies. 2 , 4 , 33 , 34 , 35 During a mean follow-up time of 5.4 years, KTRs with both early (6 months) and late (2 years) anemia reported a significantly higher percentage of graft failure at 4 years than did patients without anemia. 4 In a cohort of 1,139 KTRs (412 anemic), during a median of 5.5 year follow-up, the presence of severe anemia (hemoglobin [Hb] concentration of <11 g/dL) was significantly associated with death-censored graft failure, the association being weaker for mild anemia.…”
Section: Causes Of Posttransplant Anemiamentioning
confidence: 97%
“…A recent meta-analysis and systematic review showed a significantly increased risk of CVD death and major adverse cardiovascular events in anemic KTRs when compared with those without anemia. 35 …”
Section: Causes Of Posttransplant Anemiamentioning
confidence: 99%
“…A recent meta-analysis indicated that post-transplantation anemia was linked to higher overall mortality (pooled risk ratio = 1.72 [1.39, 2.13], I2 = 56%), graft loss (pooled risk ratio = 2.28 [1.77, 2.93], I2 = 94%), cardiovascular death (pooled risk ratio = 2.06 [1.35, 3.16], I2 = 0%), and cardiovascular events (pooled risk ratio = 1.33 [1.10, 1.61], I2 = 0%). Early anemia (≤6 months) carried a higher risk of overall mortality and graft loss compared to late anemia (>6 months), with a pooled risk ratio of 2.63 (95% CI 1.79-3.86; I2 = 0%) and 2.96 (95% CI 2.29-3.82; I2 = 0%), respectively [50]. An open-label French multicenter randomized controlled trial investigated the effect of epoetin-β on normalizing hemoglobin values (13.0-15.0 g/dL, n = 63) versus partial correction of anemia (10.5-11.5 g/dL, n = 62) in transplant recipients with hemoglobin < 11.5 g/dL and estimated creatinine clearance (eCrCl) < 50 mL/min per 1.73 m 2 .…”
Section: Haematological Disorders: Leukopenia and Anemiamentioning
confidence: 99%